PENGARUH SISTEM DIGITAL AKUNTANSI TERHADAP KUALITAS PENGAMBILAN KEPUTUSAN DENGAN MODEL MEDIASI DAN MODERASI - Yulizar, Johan; Julisar (Jurnal Kontemporer Akuntansi, 2025)
The research began with the rapid development of information technology, the business world experience fundamental change in term of data management and financial information. The transition of accounting systems to the digital era is must for companies that want to remain relevant and competitive in the current era of globalization. Digital accounting systems allow companies to improve the efficiency of company operation, reduce the risk of human error, and real-time access to financial data needed for strategic decision making for the company. To get the right decision making there are several factors, namely data quality, system quality, information quality and analytical decision making culture. Therefore, this research hypotesizes that these four factor have positive and significant effect on decision making quality. To validate the hypotesizes, this research uses the Structural Equation Modeling (SEM) analysis technique using SmartPLS 4.1.0.2 software. The result of statistical test show that some hypotesizes can be accepted. Thus data quality, system quality, information quality and analytical decision making culture play important role in decision making quality, thereby increasing business competition in Indonesia.